2020
DOI: 10.1101/2020.04.01.20049999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fear avoidance beliefs limit lumbar spine flexion during object lifting in pain-free adults

Abstract: There is a long-held belief that physical activities such as lifting with a flexed spine is generally harmful for the back and can cause low back pain (LBP), potentially nurturing fear avoidance beliefs underlying pain-related fear. In chronic LBP patients, pain-related fear has been shown to be associated with reduced lumbar range of motion during lifting, indicating distinct and probably protective psychomotor responses to pain. However, despite short term beneficial effects for tissue health, recent eviden… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
(107 reference statements)
1
3
0
Order By: Relevance
“…Indeed, Matheve et al (2019) only identified a negative association with movement in the lumbar region during lifting with a measure directly quantifying fear of lifting, but not with common assessment tool for fear of movement. Further research confirmed analogous findings in people without pain (Knechtle et al, 2021) and by referring to such results, other researchers emphasized that more targeted assessments should be used (Christe et al, 2021). This argument is contradicted by the results of a study by Karayannis et al (2013) who found that fear of movement assessed with the TSK was linked to rigidity of the trunk, but not an item that was designed to capture fear of the task used for the rigidity assessment.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Indeed, Matheve et al (2019) only identified a negative association with movement in the lumbar region during lifting with a measure directly quantifying fear of lifting, but not with common assessment tool for fear of movement. Further research confirmed analogous findings in people without pain (Knechtle et al, 2021) and by referring to such results, other researchers emphasized that more targeted assessments should be used (Christe et al, 2021). This argument is contradicted by the results of a study by Karayannis et al (2013) who found that fear of movement assessed with the TSK was linked to rigidity of the trunk, but not an item that was designed to capture fear of the task used for the rigidity assessment.…”
Section: Introductionsupporting
confidence: 65%
“…For this directional fear assessment, a custom question type was used. Earlier studies, which had integrated fear assessments more directly related to the movements under investigation, appended further items to the PHODA-SEV (Karayannis et al, 2013) or used items already available within the PHODA-SEV (Matheve et al, 2019;Knechtle et al, 2021). Similar to the style of the PHODA-SEV, the participants rated how harmful they perceive bending the trunk in different directions (Figure 1).…”
Section: Fear Of Movementmentioning
confidence: 99%
“…However, the predictive value of pain-related fear regarding the development of LBP is limited ( 39 ) and psychological factors in general (when considered in isolation) explain only a small proportion in outcomes such as pain intensity ( 44 , 45 ). Yet, recent research has shown an association between pain-related fear and dysfunctional motor behavior in LBP patients and healthy individuals ( 46 48 ), indicating significant interactions between psychological factors and motor control (psychomotor interactions), which can promote potential clinically relevant consequences such as limited motor variability, increased paraspinal muscle co-contraction and loading on spinal tissues ( 15 ). Research on the role of pain-related fear in LBP should therefore systematically involve measures of motor control (such as spinal movement biomechanics) to identify potential pain-provoking interactions.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…The most common self-reporting tools for assessing pain-related fear are questionnaires based on psychological constructs such as fear of movement/(re)injury [Tampa Scale for Kinesiophobia, TSK ( 51 )], perceived harmfulness of daily activities [Photograph Series of Daily Activities, PHODA ( 52 )] or fear avoidance beliefs [Fear Avoidance Beliefs, FABQ ( 53 )]. However, it must be noted that even though recent neuroscientific and biomechanical evidence supports the diversity of pain-related fear constructs ( 46 , 48 , 54 ), it is still unclear how specific the different questionnaires are in assessing the various psychological constructs ( 55 ). Combining these questionnaires with biomechanical and neuroscientific measures might lead to a better understanding of the underlying psychological constructs.…”
Section: Building Bridges: a Cross-disciplinary Approachmentioning
confidence: 99%